1. The problem statement, all variables and given/known data is a) fg''-f''g=(fg'-f'g)' b) fg''+f''g=(fg)'' 2. Relevant equations product formula? f'g+fg'=fg' quotient rule- (f'g-fg')/g^2=(f/g)' 3. The attempt at a solution All i did was plug in numbers, such that f=x^3 and g=x^2 and then solved it that way. For doing this, I got that a is true and that b is false, but it isn't really a proof if you use numbers, hell it isn't a proof at all. Any ideas on how to make it so that it either IS or ISNT true.